Genre-Based Indonesian Language Learning Scientific Approach and Method - Mahsun Mahsun; Baiq Wahidah; Muhammad Khairussibyani; Yenni Febtaria Wijayatiningsih (Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This study aims to analyze the scientific approach and method of learning and show the results in genre-based Indonesian language learning. This study used a qualitative approach. The data were collected from three sources: literature review, student learning outcomes, and questionnaire results. Data on students’ learning outcomes and views were explicitly taken from two groups. The first group consisted of 113 respondents who were asked to construct literary texts. The second group consisted of 105 respondents who were asked to construct exposition texts. The library research data was analyzed using theoretical and conceptual analysis, while the students’ learning outcome data were analyzed qualitatively and quantitatively. The data from the questionnaire were analyzed by quantitative analysis. Based on the analysis of the three forms of data, it was discovered that; (a) the terms scientific approach and method were relevant to genre-based (Indonesian) language learning, (b) scientific as a learning method (scientific method) could be used by teachers as a method in delivering learning material as well as by students to construct texts as a form of learning outcomes, (c) scientific method guides students to construct text systematically, in controlled, empirically, and analytically through scientific stages, and (d) there was a gap between the views of the students who think that the scientific method could guide students in constructing text and enhancing the quality of text production. With a score of 41.43, 91.15% of the students in the first group believed that the scientific approach might help students produce texts with high-quality output outcomes. 90% of the 105 respondents in the second group said that the scientific approach might help students create explanation texts even though the degree of text creation quality is low (score: 49.5). The students’ less expressive language use was to blame for this.